PENGARUH PEMBERIAN SUSU KAMBING TERHADAP GAMBARAN MIKROSKOPIS GINJAL TIKUS WISTAR YANG TERPAPAR ASAP KENDARAAN BERMOTOR - Eko Djatmikanto Satrio N.; Fanti Saktini (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background: Kidney is an important organ which filtrates foreign substance in the body. Vehicle exhaust fumes contain lead metals that impair renal function by affecting the hemodynamic, immunology, and metabolic systems. Goat milk contains zinc and iron which acting as competitive inhibitors for lead in the digestive system. It also contains antioxidants to prevent tissue damage caused by Reactive Oxygen Species (ROS).  Aim: To prove the effect of goat milk to renal microscopic structure in rats contaminated with vehicle exhaust fumes.Methods: This research was true experimental with post-test only controlled group design. Samples were 15 Wistar rats age 2-3 months and randomly divided into 3 groups. Control group (K) was given standard feeding only; experiment group 1 (P1) was given standard feeding and exhaust fumes exposure; experiment group 2 (P2) was given standard feeding, exhaust fumes exposure and goat milk. The exposure was 8 hours/day for 30 days while goat milk’s dose was 473.2 mg per kilogram weight body. At 31th day, rats was terminated to examine their kidney microscopic appearance. Data was then analyzed using Kruskall-Wallis test followed by Mann-Whitney test.Result: This study showed that the kidney tubules damage percentage (albuminous degeneration) in experiment groups were significantly different compared with control group (p<0.05). In the other hand, the kidney tubules damage between two experiment groups (P1-P2) was insignificant (p=0,093), despite the damage was more severe in P1 compared to P2.Conclusion: Exhaust fumes exposure affected kidney microscopic structure. Goat milk has no effect on kidney microscopic structure that exposed with vehicle exhaust fumes.